EFFECTIVE AYURVEDIC TREATMENT ON LEUCODERMA IN EARLY STAGE- A CASE REPORT - Shreya Umesh Sawant; Jayant Subhash Hartalkar (International Journal of Applied Ayurved Research, 2015)
Leucoderma appears to affect at least 1% to 2% of population, it is usually harmless but for cosmetic reasons, it is nuisance to those who have it. It is characterized by loss of pigmentation of skin.Acoording to Ayurveda, this condition can be treated as Shvitra which gives effective results without any side effect. A patient of Leucoderma treated as a Shvitra with traditional Ayurvedic treatment is presented in this case study.